The influence of modern PR technologies on enhancing the competitiveness of a trade enterprise - Zakrevska, Liudmyla; Strashynska, Larysa; Dankeieva, Oksana (Management and Entrepreneurship: Trends of Development, 2025)
The article examines the role of modern PR technologies in ensuring the competitiveness of enterprises. Competitiveness is defined as the ability of an enterprise to function effectively, adapt to dynamic changes and ensure stable growth of market share. Modern PR tools are systematized and their impact on the competitiveness of a trading enterprise is determined. The strategic management function in the modern sense belongs to PR. This will allow the formation of long-term relationships with stakeholders, increase reputational capital and create intangible assets of the enterprise. A model of the impact of modern PR technologies on the competitiveness of a trading enterprise is built. Integrated indicators of the competitiveness of leading domestic trading enterprises using PR tools are calculated. Integration of PR technologies into the competitiveness management system contributes to increasing customer loyalty, strengthening a positive brand image and forming sustainable competitive advantages in the long term. The purpose of the article is a comprehensive study of the impact of modern PR technologies on the competitiveness of a trading enterprise and an analysis of their role in the formation of an effective corporate communications system. Methodology: a method of cognition based on a systemic approach, the principle of complexity and consistency in the cognition of economic phenomena and processes, empirical research with consumer surveys and analysis of open data of trading enterprises, an integral-analytical method, a graphical method. The results of the study showed that an effective combination of traditional and digital PR tools significantly affects the competitiveness of the enterprise, increasing brand recognition, the level of customer loyalty, market share and the effectiveness of communication campaigns.JEL Classification: M31, M37, L81, M21